2016
DOI: 10.1007/s40258-015-0218-x
|View full text |Cite
|
Sign up to set email alerts
|

The Urolift System for the Treatment of Lower Urinary Tract Symptoms Secondary to Benign Prostatic Hyperplasia: A NICE Medical Technology Guidance

Abstract: As part of its Medical Technologies Evaluation Programme (MTEP), the National Institute for Health and Care Excellence (NICE) invited Neotract (manufacturer) to submit clinical and economic evidence for their prostatic urethral lift device, Urolift, for the relief of lower urinary tract symptoms secondary to benign prostatic hyperplasia (LUTS BPH). The Urolift System uses implants to retract the prostatic lobe away from the urethral lumen. The clinical evidence used in the manufacturer’s submission shows that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 29 publications
1
30
0
Order By: Relevance
“…It may also be of interest to compare PAE with the UroLift implant, as this presents another emerging, less invasive alternative to transurethral surgical options. Our findings in the UK‐ROPE study are very similar to those presented in a recent meta‐analysis, which reported the following improvements at 12‐months post‐Urolift treatment: an IPSS improvement of −10.5 points, a QoL improvement of −2.3 points, a clinically non‐significant +0.8 point improvement in IIEF score, a +3.5‐mL/s improvement in Q max , and a small improvement in PVR of −5.7 mL . That study also presented economic data in which day‐case Urolift treatment was cost‐saving compared with inpatient TURP and HoLEP.…”
Section: Discussionsupporting
confidence: 89%
“…It may also be of interest to compare PAE with the UroLift implant, as this presents another emerging, less invasive alternative to transurethral surgical options. Our findings in the UK‐ROPE study are very similar to those presented in a recent meta‐analysis, which reported the following improvements at 12‐months post‐Urolift treatment: an IPSS improvement of −10.5 points, a QoL improvement of −2.3 points, a clinically non‐significant +0.8 point improvement in IIEF score, a +3.5‐mL/s improvement in Q max , and a small improvement in PVR of −5.7 mL . That study also presented economic data in which day‐case Urolift treatment was cost‐saving compared with inpatient TURP and HoLEP.…”
Section: Discussionsupporting
confidence: 89%
“…In September 2013, the US Food and Drug Administration approved the UroLift. In September 2015, the UK National Institute for Clinical and Health Excellence also approved the UroLift as an effective, safe and cost-effective treatment for use in the UK health system, when implemented in a day-case setting [6] , [12] . It has been postulated that even earlier management with PUL may even reduce overall cost for those patients managed with medication.…”
Section: Pulmentioning
confidence: 99%
“…1 The UroLift procedure is undertaken transurethrally with either general or local anesthesia. 8 The UroLift device works by introducing a single-use, pre-loaded delivery device through a rigid sheath under cystoscopic visualization. The delivery device then deploys permanent, trans-prostatic, Nitinol implants to retract the lobes of the prostate towards the capsule.…”
Section: Discussionmentioning
confidence: 99%
“…The delivery device then deploys permanent, trans-prostatic, Nitinol implants to retract the lobes of the prostate towards the capsule. 8 Typically, multiple implants are used to retract the obstructing lateral lobes and create an open, continuous voiding channel 1 (Figure 4).…”
Section: Discussionmentioning
confidence: 99%